Emerging intelligent wearable devices for cardiovascular health monitoring - Wang, Yiqian; Zou, Yang; Li, Zhou (Nano today, 2024)
Cardiovascular diseases have long posed a significant threat to human health. Wearable devices are increasingly vital in cardiovascular health monitoring, disease screening, and early warning because of their non-invasiveness, real-time data provision and continuous monitoring capability. The collection, processing, and analysis of data in cardiovascular health monitoring involve numerous repetitive and standardized tasks, where artificial intelligence (AI) technology plays a pivotal role. AI is particularly effective in handling large volumes of data, thus enhancing the diagnostic and predictive capabilities of wearable devices. This review summarizes essential indicators for assessing cardiovascular health and provides a comprehensive introduction to commonly used non-invasive monitoring methods, including pulse pressure, photoplethysmography, electrocardiogram, bioimpedance analysis, seismocardiography/ ballistocardiography, and ultrasonography. Additionally, some impressive advances in wearable cardiovascular health monitoring technologies are reviewed and their integration with AI is highlighted, demonstrating typical application cases from recent years. Finally, the review discusses the current challenges of integrating AI into wearable devices for cardiovascular health monitoring, focusing on aspects from device design, algorithm optimization, comfort, reliability, and security. With the seamless integration of AI and wearable devices, a new generation of wearable intelligent devices promises to revolutionize the monitoring, prevention and management strategies of cardiovascular diseases. [Display omitted] •Summary of key physiological indicators for cardiovascular health and their non-invasive monitoring methods.•Analysis of material, performance, forms, and applications of wearable cardiovascular health monitoring devices.•Review advances in wearable cardiovascular monitoring technology and their integration with artificial intelligence.•Summarize challenges and future directions in wearable cardiovascular devices: materials, design, algorithms, reliability.